Addition of Pregabalin to Multimodal Analgesic Therapy Following Ankle Surgery: A Randomized Double-Blind, Placebo-Controlled Trial. Issue 3 (1st May 2012) - YaDeau, Jacques T.; Paroli, Leonardo; Kahn, Richard L.; Jules-Elysee, Kethy M.; LaSala, Vincent R.; Liu, Spencer S.; Lin, Edward; Powell, Karlyn; Buschiazzo, Valeria L.; Wukovits, Barbara; Roberts, Matthew M.; Levine, David S.
Abstract : Background and Objectives: Pregabalin is often used as a perioperative analgesic adjunct; some studies show benefit, but others do not. Adverse effects, such as confusion and sedation, have been attributed to perioperative use of pregabalin. We tested the hypothesis that pregabalin, when used as part of a multimodal analgesic regimen, reduces the duration of moderate to severe pain in the first 24 hrs following foot or ankle surgery. Secondary outcomes included measures of opioid and pregabalin adverse effects. Methods: Sixty patients scheduled for hospital admission after foot or ankle surgery entered this randomized, double-blind, placebo-controlled trial. Patients received a neuraxial anesthetic, a popliteal fossa sciatic nerve block using 30 mL 0.375% bupivacaine with clonidine 100 µg and epinephrine, a saphenous nerve block, postoperative hydromorphone intravenous patient-controlled analgesia, and oral analgesics (oxycodone/acetaminophen). Patients were randomized to receive pregabalin (100 mg preoperatively, then 50 mg every 12 hrs) or a placebo for 3 days. The primary outcome was the number of hours that patients reported moderate to severe pain. Results: Both groups reported a similar number of hours of moderate to severe pain during the first 24 hrs: 4.1 (SD, 4.1) hrs (pregabalin) versus 4.5 (SD, 3.5) hrs (placebo). Pain scores, opioid use, and adverse effects were also similar in both groups. Conclusions: No clinical benefit was obtained from perioperative administration of pregabalin (100 mg preoperative, then 50 mg every 12 hrs) as part of a multimodal postoperative analgesic regimen following foot and ankle surgery.